Pengaruh Ukuran Perusahaan Dan Opini Audit Terhadap Terjadinya Auditor Switching Dengan Dimoderasi Oleh Reputasi Auditor : Studi Kasus Pada Perusahaan Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Naula Chantika Putri F; Hwihanus Hwihanus (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research is quantitative research which aims to determine and test the influence of company size, audit opinion, reputation of public accounting firms and auditor switching. This research uses annual financial report data on transportation and logistics sector companies that are listed on the Indonesia Stock Exchange (BEI) in the 2020-2022 period. Testing this research hypothesis uses logistic regression analysis with the SPSS 26 program with a significance level of 5.5% (0.55). The results of this research test state that partially 1) the audit opinion variable has no effect and has a negative value on auditor switching; 2) the public accounting firm's reputation variable has no effect but has a positive value on auditor switching. 3) auditor reputation has no effect and has a negative value on auditor switching and does not affect the condition of the company.